Initiation of minute virus of mice DNA replication is regulated at the level of origin unwinding by atypical protein kinase C phosphorylation of NS1 - Nüesch, Jürg P. F.; Christensen, Jesper; Rommelaere, Jean (Journal of virology, 2001)
Minute virus of mice nonstructural protein NS1 is a multifunctional protein that is involved in many processes necessary for virus propagation. To perform its distinct activities in timely coordinated manner, NS1 was suggested to be regulated by posttranslational modifications, in particular phosphorylation. In fact, NS1 replicative functions are dependent on protein kinase C (PKC) phosphorylation, most likely due to alteration of the biochemical profile of the viral product as determined by comparing native NS1 with its dephosphorylated counterpart. Through the characterization of NS1 mutants at individual PKC consensus phosphorylation sites for their biochemical activities and nickase function, we were able to identify two target atypical PKC phosphorylation sites, T435 and S473, serving as regulatory elements for the initiation of viral DNA replication. Furthermore, by dissociating the energy-dependent helicase activity from the ATPase-independent trans esterification reaction using partially single-stranded substrates, we could demonstrate that atypical PKC regulation of NS1 nickase activity occurs at the level of origin unwinding prior to trans esterification.